Could deep brain stimulation be a possible solution for acquired hypothalamic obesity?. Issue 3 (March 2023) - Dassen, Amber R.; van Schaik, Jiska; van den Munckhof, Pepijn; Schuurman, P.R.; Hoving, Eelco W.; van Santen, Hanneke M.
Abstract: Objective: Hypothalamic dysfunction may result in morbid obesity as a consequence of decreased energy expenditure, decreased feelings of satiety, and increased fat storage. In patients with hypothalamic dysfunction, neurobehavioral dysfunction is also often present. Currently, no effective treatment has been found for hypothalamic obesity (HO). We hypothesize that deep brain stimulation (DBS) may be an effective treatment for patients with hypothalamic dysfunction, aiming to treat HO as well as the neurobehavioral dysfunction. Methods: A systematic search was conducted in the PubMed, EMBASE and Cochrane Library databases for studies published until May 2022 reporting on DBS for the treatment of HO. Results: Three studies met the predetermined inclusion criteria, with in total six patients treated with DBS for HO, of which five patients with Prader-Willi syndrome (PWS) and one patient with HO after treatment for craniopharyngioma (CP). Targets of DBS included the lateral hypothalamic area (LHA) and the nucleus accumbens (NAcc). In patients with PWS, LHA-DBS was associated with a mean increase of Body Mass Index (BMI) (+5.8%), with no change in hormonal levels, results of blood workup, sleep, or neuropsychological evaluation. In the patient with CP, NAcc-DBS was associated with a decrease in BMI (−8.7%) and a subjective increase in mental health, energy and willingness to act, and no feeling of increased appetite. No objective measurements on neurobehavioral function were reported. No severe adverse events were reported in these cases. Mild to moderate adverse events included hypomanic symptoms and infection. All patients with a described follow-up period ( n = 5) were able to sustain the treatment for at least 6 months with few interruptions. Conclusion: There is limited research reporting on DBS for HO. The effectiveness differed across studies and the evidence is limited. Although there may be potential for DBS treatment in the severe-refractory condition of HO in patients with CP, more research is needed for target selection and evaluation of effectiveness.